Determinan Pola Konsumsi Siswa Jurusan IPS SMA Negeri Di Kabupaten Ogan Komering Ilir - Tri Fitriani; Heri Yanto; Muhsin Muhsin (Jurnal Pendidikan Ekonomi, 2021)
The consumption pattern is the proportion of the total expenditure of an individual in meeting a need. The purpose of this study was to analyze the determinants of consumtion pattern of students majoring in social Studies at Senior High School in Ogan Komering Ilir regency with financial literacy as intervening variable. The population of this study is senior high school students in Ogan Komering Ilir regency, totaling 5281 students. The sample size in the study used the Slovin formula, which was obtained by 372 students. The sampling technique was carried out by Cluster Random Sampling. The data collection method is in the form of a questionnaire. Data analysis used descriptive statistics, path analysis, and Sobel tests. The results showed that (1) peer group had a positive and significant effect on consumption patterns, (2) the role of the family had a positive and significant effect on consumption patterns, (3) religiosity had a positive and significant effect on consumption patterns, (4) financial literacy had a positive and significant effect. on consumption patterns, (5) peer group have a positive and significant effect on consumption patterns through financial literacy, (6) the role of the family has a positive and significant effect on consumption patterns through financial literacy, (7) religiosity has a positive and significant effect on consumption patterns through financial literacy, (8) the role of the family has a positive and significant effect on peer group, and (9) the role of the family has a positive and significant effect on religiosity. DOI: https://dx.doi.org/10.17977/UM014v14i22021p145